Rapid prototyping for DFM - Drozba, Thomas J.; Bollinge, Steven R.; Robinson, Adrian (Manufacturing insights, 1991)
Outlines six rapid prototype technologies: stereolithography, laser modeling, solid based curing, selective laser sintering, fused deposition modeling, laminated object manufacturing. Also includes case studies in various industries.